Synergistic effects between amoxicillin, metronidazole, and the hydroxymetabolite of metronidazole against Actinobacillus actinomycetemcomitans. - Pavicić, M J (1991)
Interactions between metronidazole and amoxicillin, metronidazole and its hydroxymetabolite, and amoxicillin and the hydroxymetabolite of metronidazole were investigated with checkerboard titrations in combination with accurately determined MICs and MBCs. Actinobacillus actinomycetemcomitans was used as the test organism. Synergism was found for all three combinations. Fractional inhibitory concentration indices and fractional bactericidal concentration indices varied from 0.3 to 0.7. These synergistic interactions between these antibiotics may explain the efficacy of the combination of metronidazole and amoxicillin in various bacterial infections, including periodontal disease.